2020
DOI: 10.1128/mcb.00663-19
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1 Homodimers and Heterodimers Orchestrate Lineage-Specific Differentiation

Abstract: The extensive array of basic helix-loop-helix (bHLH) transcription factors and their combinations as dimers underpin the diversity of molecular function required for cell type specification during embryogenesis. The bHLH factor TWIST1 plays pleiotropic roles during development. However, which combinations of TWIST1 dimers are involved and what impact each dimer imposes on the gene regulation network controlled by TWIST1 remain elusive. In this work, proteomic profiling of human TWIST1-expressing cell lines and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Differential binding analysis of TWIST1 using sum-normalized peptide-spectrum match (PSM) values ( Figure 1—figure supplement 2B,C ; see Materials and methods) revealed 140 putative TWIST1 interactors in NCCs (p<0.05; Fold-change >3; PSM#>2; Figure 1B , Supplementary file 1 ). These candidates included 4 of 56 known TWIST1 interactors, including TCF3, TCF4, TCF12, and GLI3 (overlap odds ratio = 18.05, Chi-squared test p-value=0.0005; Agile Protein Interactomes DataServer [APID]) ( Alonso-López et al, 2019 ; Fan et al, 2020 ). Despite that the APID database covers a broad spectrum of protein interaction in different cell line models, it was noted that the TWIST1 partners, TCF3, 4, and 12 that were recurrently identified in yeast-two-hybrid, immunoprecipitation and in vitro interaction assays were recovered by BioID ( El Ghouzzi et al, 2000 ; Firulli et al, 2007 ; Fu et al, 2011 ; Teachenor et al, 2012 ; Sharma et al, 2013 ; Kotlyar et al, 2015 ; Li et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Differential binding analysis of TWIST1 using sum-normalized peptide-spectrum match (PSM) values ( Figure 1—figure supplement 2B,C ; see Materials and methods) revealed 140 putative TWIST1 interactors in NCCs (p<0.05; Fold-change >3; PSM#>2; Figure 1B , Supplementary file 1 ). These candidates included 4 of 56 known TWIST1 interactors, including TCF3, TCF4, TCF12, and GLI3 (overlap odds ratio = 18.05, Chi-squared test p-value=0.0005; Agile Protein Interactomes DataServer [APID]) ( Alonso-López et al, 2019 ; Fan et al, 2020 ). Despite that the APID database covers a broad spectrum of protein interaction in different cell line models, it was noted that the TWIST1 partners, TCF3, 4, and 12 that were recurrently identified in yeast-two-hybrid, immunoprecipitation and in vitro interaction assays were recovered by BioID ( El Ghouzzi et al, 2000 ; Firulli et al, 2007 ; Fu et al, 2011 ; Teachenor et al, 2012 ; Sharma et al, 2013 ; Kotlyar et al, 2015 ; Li et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…TWIST1, EMT-promoting transcription factor, is an essential for cancer metastasis [ 49 ]. A recent report revealed that the TWIST1 homodimer and heterodimer interactions with E-proteins, such as TCF3/E2A, TCF4/ITF-2, and TCF12/HEB, enhances EMT [ 50 ]. Among those, the class I bHLH factor, TCF4, is one of the last additions among the EMT regulating factors, and acts as an E-cadherin repressor by interacting with other molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, certain post-translational modifications can also affect DNA binding of bHLH factors. Phosphorylation of Serines or Threonines in the basic (e.g., HAND, Hes1, NeuroM (NeuroD4) and myogenic factors) [101][102][103][104], HLH (e.g., Twist1, HAND, and Neurogenin/Achaete-Scute/Atonal subfamilies) [70,101,105,106] and other (e.g., Max) [107] domains can impede DNA binding of the mentioned factors.…”
Section: Dna-motif Preferencesmentioning
confidence: 99%